Analisis Kebijakan Penyelenggaraan Program Studi Umum di Perguruan Tinggi Keagamaan Islam: Arah, Tantangan, dan Implikasinya Terhadap Identitas PTKI - Feri Rustandi; Dul WahidToha (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study aims to analyze the policy direction, implementation challenges, and implications of offering general (non-religious) study programs for the institutional identity of Islamic Religious Higher Education Institutions (Perguruan Tinggi Keagamaan Islam, PTKI) in Indonesia. It employs a qualitative approach through document study and content analysis of official regulations, technical guidelines, and institutional documents related to fields of study, academic degrees, authorization to offer study programs, program naming, and institutional development. The findings show that the policy direction is shaped by a combination of regulations issued by the Ministry of Religious Affairs, which governs religious mandates, fields of study, academic degrees, and procedures for granting licenses to offer study programs, and regulations issued by the Ministry of Education, Culture, Research, and Technology, which govern the naming and official list of study programs within the national higher education system. As a result, general study programs at PTKI are nationally recognized but still situated within the framework of religious fields of study. At the implementation level, however, a number of challenges emerge, including potential interpretive tensions between the two regulatory regimes, limited institutional capacity and human resources, a gap between the vision of knowledge integration and classroom practices that remain dichotomous, the complexity of implementing the “Merdeka Belajar–Kampus Merdeka” policy, and cultural as well as identity politics dynamics. These factors make the implications of general study programs for PTKI’s identity ambivalent: they can strengthen PTKI’s identity as modern Islamic universities if designed within a robust framework of knowledge integration, religious moderation, and quality management, but they can also erode PTKI’s epistemological distinctiveness if developed merely as a pragmatic response to market demands and accreditation pressures without clear internal policy support and an explicit epistemological design.